New Generalizations of the Scorza-Dragoni Theorem - Gaidukevich, O. L.; Maslyuchenko, V. K. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We consider Carathéodory functions f : T × X → Y, where T is a topological space with regular σ-finite measure, the spaces X and Y are metrizable and separable, and X is locally compact. We show that every function of this sort possesses the Scorza-Dragoni property. A similar result is also established in the case where the space T is locally compact and X = ℝ∞.